2016
DOI: 10.5941/myco.2016.44.4.217
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Wood-Inhabiting Polyporoid and Corticioid Fungi in Odaesan National Park, Korea

Abstract: Polyporoid and corticioid fungi are among the most important wood-decay fungi. Not only do they contribute to nutrient cycling by decomposing wood debris, but they are also valuable sources for natural products. Polyporoid and corticioid wood-inhabiting fungi were investigated in Odaesan National Park. Fruit bodies were collected and identified based on morphological and molecular analyses using 28S and internal transcribed spacer regions of DNA sequences. As a result, a total of 149 species, 69 genera, 22 fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…As far as we know their distribution areas do not overlap. Although we have examined only one collection from Northeast China, available ITS sequences indicate that the species is widespread in China and Korea (Shen et al 2014, Kim et al 2015, Jang et al 2016.…”
Section: Distribution and Ecologymentioning
confidence: 99%
“…As far as we know their distribution areas do not overlap. Although we have examined only one collection from Northeast China, available ITS sequences indicate that the species is widespread in China and Korea (Shen et al 2014, Kim et al 2015, Jang et al 2016.…”
Section: Distribution and Ecologymentioning
confidence: 99%
“…Morphologically, Lopharia s.s. is distinct from Dentocorticium and Dendrodontia but are phylogenetically closely related as shown in phylogenetic studies based on two to six taxa (Yoon et al 2003, Wu et al 2007, Justo and Hibbett 2011, 2017, Jang et al 2016). In this study, eleven taxa of Lopharia s.s., Dentocorticium , Dendrodontia and Fuscocerrena from North America and East Asia were included in phylogenetic analyses of a concatenated 3-gene dataset of ITS, 28S and rpb2 sequences.…”
Section: Introductionmentioning
confidence: 73%
“…A few phylogenetic studies that have included Lopharia s.s. and Porostereum spadiceum (Pers.) Hjortstam & Ryvarden (generic type) showed that they are distantly related (Ko et al 2001, Yoon et al 2003, Wu et al 2007, Jang et al 2016). Both genera are included in the Polyporales with Lopharia in the Polyporaceae and Porostereum in the Phanerochaetaceae (Justo et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The genus is characterized by astrocystidia and halocystidia in hymenium [ 42 ]. R. pinicola was reported in the list of polyporoid and corticioid fungi without morphological description [ 43 ]. For this reason, we suggest R. pinicola as an unrecorded species in Korea.…”
Section: Resultsmentioning
confidence: 99%